Iodised Salt: Processing, Determination and Impact on Health - Hassan, Norazlinda Ghul; Hamid, Mansoor Abdul; Julmohammad, Norliza binti (Proceeding International Conference on Religion, Science and Education, 2026)
Iodine is an essential micronutrient required for the synthesis of thyroid hormones that regulate growth, metabolism, and neurological development. Despite extensive global efforts, iodine deficiency remains a significant public health concern, particularly in developing regions, leading to disorders such as goitre, hypothyroidism, and cognitive impairment. Universal Salt Iodisation (USI) is recognised as the most effective and sustainable strategy to prevent iodine deficiency disorders (IDD). This study reviews the processing techniques, analytical determination, and health implications of iodised salt. Iodisation is typically achieved by incorporating potassium iodate (KIO3) or potassium iodide (KI) into edible salt through methods such as dry mixing method, drip-feed process, spraying method, refining process or vacuum evaporation process to ensure uniform distribution and stability. Accurate determination of iodine content is essential to evaluate fortification quality and consumer safety. Analytical methods include iodometric titration, UV-Vis spectrophotometer and High Performance Liquid Chromatography (HPLC), each differing in sensitivity and precision. Environmental factors such as humidity, temperature, and light exposure significantly affect iodine retention during processing and storage. Adequate intake of iodised salt has been shown to markedly reduce IDD prevalence and enhance thyroid health across populations. However, continuous monitoring is vital to avoid both deficiency and excessive iodine intake. The findings underscore the importance of standardized iodisation processes, rigorous quality control, and effective policy implementation to maintain optimal iodine nutrition globally.